STRATEGI PENGEMBANGAN KAWASAN BUMI PERKEMAHAN KEPURUN KLATEN DENGAN PENDEKATAN ARSITEKTUR EKOLOGIS - Ayu Ratna Pertiwi; Sri Yuliani; Agus Heru Purnomo (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
The development of Kepurun Camping Ground in Klaten with Ecological Architecture is motivated by the existing condition of the Camping Ground after being temporary shelter while the eruption of Mount Merapi in 2010 has a change function and can not longer be used for camping activities. Kepurun Camping Ground is the only camping ground in Klaten that organized by Kwartir Cabang Klaten, it is necessary to do the refunction and also the development of facility to reactivate the KepurunCamping Ground as a place of camping activity in Klaten. The method used is the architectural method which is the essence of ecologycal architecture according to Heinz Frick and Kenneth Yeang according to the design of Kepurun Camping Ground. Then combine the essence of Architectural Ecology into the design. The strategy in essence design is the result of interaction between earth, nature, and natural potential existing of Kepurun Camping Ground is a camping facility, such as, hall, agrotourism area, and out bound area.